2016
DOI: 10.1016/j.tjo.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive problems related to strabismus surgery

Abstract: Strabismus surgery may be responsible for some restrictions in ocular motility that may cause new problems after surgery. Most of the time these restrictions present as a complex motility problem after surgery that requires further treatment. There may be various reasons that cause motility restriction following strabismus surgery. Those are excessive shortening or inadvertent capture of extraocular muscles, transposition procedures and, the most challenging problem, postoperative scar tissue-adhesion formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…study showed that possible causes of this kind of sensory disorders could decrease in VA caused by subretinal fluid and vision distortion and anisometropia due to the eye elongation by scleral buckle effect 14 . One of the most common etiologies for strabismus following SBS is mechanical adhesion which is seen in different sites such as Tenon's capsule, sclera, inter muscular septum, extraocular muscles, and orbital fat 15 . Surgical trauma induces a fibrotic reaction which causes fat adherence syndrome 16 .…”
Section: Discussionmentioning
confidence: 99%
“…study showed that possible causes of this kind of sensory disorders could decrease in VA caused by subretinal fluid and vision distortion and anisometropia due to the eye elongation by scleral buckle effect 14 . One of the most common etiologies for strabismus following SBS is mechanical adhesion which is seen in different sites such as Tenon's capsule, sclera, inter muscular septum, extraocular muscles, and orbital fat 15 . Surgical trauma induces a fibrotic reaction which causes fat adherence syndrome 16 .…”
Section: Discussionmentioning
confidence: 99%
“…50 Limitations of strabismus surgery involving postoperative scarring and the need for repeated surgery may motivate the decision to pursue refractive surgery as an alternative. [10][11][12] Through follow-up, refractive error regression after refractive surgery is well reported; however, ocular deviation changes have not been well established. 13,[53][54][55][56] Younger patients may have more extreme refractive errors than adults, and thus, it may be particularly worthwhile to counsel patients with higher refractive errors on the possibility of functionally significant visual changes over time postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…7–9 However, the formation of postoperative scar tissue can predispose recurrence and complicates future strabismus surgery, which may be required. 10–12…”
mentioning
confidence: 99%
“…Secondary restrictive strabismus should be differentiated from extraocular muscle paralytic strabismus. Restrictive strabismus can be caused by conjunctival scarring, fat adherence syndrome, or rectus muscle contracture,and so on [13]. The fat adherence syndrome is an important cause of restrictive strabismus after retina surgery and that this complication can be minimized by avoiding surgical maneuvers that violate Tenon's capsule and expose extraconal fat.…”
Section: Discussionmentioning
confidence: 99%